Dendritic cells: the yin and yang in disease progression - Jiménez-Cortegana, Carlos; Palomares, Francisca; Alba, Gonzalo; Santa-María, Consuelo; de la Cruz-Merino, Luis; Sánchez-Margalet, Victor; López-Enríquez, Soledad (Frontiers in Immunology, 2024)
Dendritic cells (DCs) are antigen presenting cells that link innate and adaptive immunity.DCs have been historically considered as the most effective and potent cell population to capture, process and present antigens to activate naïve T cells and originate favourable immune responses in many diseases, such as cancer. However, in the last decades, it has been observed that DCs not only promote beneficial responses, but also drive the initiation and progression of some pathologies, including inflammatory bowel disease (IBD). In line with those notions, different therapeutic approaches have been tested to enhance or impair the concentration and role of the different DC subsets. The blockade of inhibitory pathways to promote DCs or DC-based vaccines have been successfully assessed in cancer, whereas the targeting of DCs to inhibit their functionality has proved to be favourable in IBD. In this review, we (a) described the general role of DCs, (b) explained the DC subsets and their role in immunogenicity, (c) analysed the role of DCs in cancer and therapeutic approaches to promote immunogenic DCs and (d) analysed the role of DCs in IBD and therapeutic approaches to reduced DC-induced inflammation.Therefore, we aimed to highlight the "yin-yang" role of DCs in cancer and IBD, two pathologies in which the dual role of DCs is well establishedto improve the understand of this type of cells in disease progression.